C(sp2)–C(sp2) cross coupling reaction catalyzed by a water-stable palladium complex supported onto nanomagnetite particles. (3rd November 2014) - Azadbakht, Tahereh; Zolfigol, Mohammad Ali; Azadbakht, Reza; Khakyzadeh, Vahid; Perrin, David M.
Abstract : A new palladium nanoparticles-based magnetic catalyst, which is stable in water, has been successfully synthesized, characterized and employed for the Suzuki reaction. Abstract : A water-stable palladium complex supported onto nanomagnetite particles was prepared and characterized. The nanocatalyst showed excellent reusability and activity in aqueous phase processes including the C(sp 2 )–C(sp 2 ) cross coupling reactions. The advantages of the protocol are its generality, high yields, short reaction time, a cleaner reaction profile, and simplicity.